Relationship between Quality of Work Life and Job Satisfaction in Asia: A Literature Review: - Veronica Eka Desi Natalia; Anisa OS Pratama; Margareta Dewi Astuti (Journal of Business and Management Review, 2020)
Quality of work life and job satisfaction is very important in an organization so that it attracts the attention of researchers. There are a number of articles on the relationship between quality of work life and job satisfaction, especially the Asian context; but there is a dearth of literature review on such relationship.The purpose of this review is to examine the relationship between quality of work life and job satisfaction in Asia. Based on the results of the literature review from various countries and organizations in Asia, we find that quality of work life and job satisfaction have a positive and significant relationship in organizations in various countries in the Asian region.